Nutritional Ketosis Affects Metabolism and Behavior in Sprague-Dawley Rats in Both Control and Chronic Stress Environments - Brownlow, Milene L.; Jung, Seung H.; Moore, Raquel J.; Bechmann, Naomi; Jankord, Ryan (Frontiers in Molecular Neuroscience, 2017)
Nutritional ketosis may enhance cerebral energy metabolism and has received increased interest as a way to improve or preserve performance and resilience. Most studies to date have focused on metabolic or neurological disorders while anecdotal evidence suggests that ketosis may enhance performance in the absence of underlying dysfunction. Moreover, decreased availability of glucose in the brain following stressful events is associated with impaired cognition, suggesting the need for more efficient energy sources. We tested the hypotheses that ketosis induced by endogenous or exogenous ketones could: a) augment cognitive outcomes in healthy subjects; and b) prevent stress-induced detriments in cognitive parameters. Adult, male, Sprague Dawley rats were used to investigate metabolic and behavioral outcomes in 3 dietary conditions: ketogenic (KD), ketone supplemented (KS), or NIH-31 control diet in both control or chronic stress conditions. Acute administration of exogenous ketones resulted in reduction in blood glucose and sustained ketosis. Chronic experiments showed that in control conditions, only KD resulted in pronounced metabolic alterations and improved performance in the novel object recognition test. The hypothalamic-pituitary-adrenal (HPA) axis response revealed that KD-fed rats maintained peripheral ketosis despite increases in glucose whereas no diet effects were observed in ACTH or CORT levels. Both KD and KS-fed rats decreased escape latencies on the third day of water maze, whereas only KD prevented stress-induced deficits on the last testing day and improved probe test performance. Stress-induced decrease in hippocampal levels of β-hydroxybutyrate were attenuated in KD group while both KD and KS prevented stress effects on BDNF levels. Mitochondrial enzymes associated with ketogenesis were increased in both KD and KS hippocampal samples and both endothelial and neuronal glucose transporters were affected by stress but only in the control diet group. Our results highlight the complex relationship between peripheral metabolism, behavioral performance and biochemical changes in the hippocampus. Endogenous ketosis improved behavioral and metabolic parameters associated with energy metabolism and cognition while ketone supplementation replicated the biochemical effects within the hippocampus but only showed modest effects on behavioral improvements.